Molecular phylogeny of the green lacewings (Neuroptera : Chrysopidae) - Winterton, S.; de Freitas, S. (Blackwell Publishing, 2006)
The first quantitative analysis of phylogenetic relationships of green lacewings (Chrysopidae) is presented based on DNA sequence data. A single nuclear and two mitochondrial genes are used in the analysis: carbomoylphosphate synthase (CPS) domain of carbamoyl-phosphate synthetase-aspartate transcarbamoylase-dihydroorotase (CAD) (i.e. rudimentary locus), large subunit ribosomal gene (16S) and cytochrome oxidase I (COI). This study represents the first use of the CAD gene to investigate phylogenetic relationships of the lacewings. DNA sequences for 33 chrysopid species from 18 genera, representing all subfamilies and tribes, were compared with outgroups sampled from families Hemerobiidae, Osmylidae and Polystoechotidae. Parsimony analyses of the combined data set recovered all of the previously established subfamilial and tribal groups as monophyletic clades (although relatively weakly supported) except Apochrysinae sensu lato. The enigmatic Nothancyla verreauxi Navas has historically been difficult to place in a subfamily group based on morphological characteristics; molecular data presented herein do not adequately resolve this problem.
Keywords: 16S; CAD; Chrysopidae; COI; molecular systematics; Neuropterida